Identification and Sequencing analysis of a P68 DEAD-box RNA helicase from Pisum sativum - Hoi, Pham Xuan; Narendra, Tuteja (VNU Journal of Science: Natural Sciences and Technology; Vol 28 No 1, 2012)
Abstract. Helicases catalyse the unwinding of energetically stable duplex DNA (DNA helicase) or inter - and intra molecular base -paired duplex RNA (RNA helicase) structures by disrupting the hydrogen bonds between the two strands and thereby plays an important role in all DNA/RNA metabolisms. Many DNA and RNA helicases share a core region of highly conserved sequence motifs, and belong to the rapidly growing DEAD-box protein family that contains the same eight conserved helicase motifs. Using 1.93 kb cDNA fragment of P68 DEAH box protein from Arabidopsis thailiana as probe for screening pea cDNA library, we identified a full length cDNA of p68 DEAH box protein that has 2058 bps with poly[A + ] tail of 28 nucleotides at the 3' end. It contains coding region of 1869 bps, 5'-end untranslated region of 53 bps and 3'-end untranslated region of 136 bps. The deduced amino acids sequence revealed a protein consisting of 623 amino acid residues with a predicted molecular mass of about 68 kDa (p68). All 8 helicase conserved domains have been observed in amino acid sequence of the protein. The nucleotide sequence alignment of Pea P68 DEAH box and homolog p68 DEAH box from different species shows that Pea P68 DEAH box has striking homology with soybean, castorbean and tomato. The deduced amino acid sequence of P68 was used for searching similar sequences with other two pea DEAH box proteins (pdh45 and p72) by using FASTA computer program reveals a common core-region around 300 amino acids that contains all the known conserved helicase domains and localizes in the middle of the genes. At molecular level, the DEAD-box RNA helicases function in process such as transcriptional regulation, regulation of RNA stability, ribosome biogenesis and post-translational regulation. Keywords: P68,  DEAD-box protein family, RNA helicase, Pisum sativum.